Long noncoding RNA NEAT1 regulate papillary thyroid cancer progression by modulating miR‐129‐5p/KLK7 expression. Issue 10 (10th May 2018) - Zhang, Hong; Cai, Yuechang; Zheng, Li; Zhang, Zhanlei; Lin, Xiaofeng; Jiang, Ningyi
Abstract : Considering the dilemma in papillary thyroid cancer treatment, this study intended to find solution in molecular respect. By probing into lncRNA‐NEAT1/miR‐129‐5p/ KLK7 interaction, this study would provide new targets for future treatment. Microarray analysis and R language package were applied to select possible lncRNA and miRNA. Luciferase reporter assay and RNA pull‐down test were employed in the detection of target relationship between lncRNA and miRNA. Clone formation assay, flow cytometry analysis, wound healing assay, and transwell assay were, respectively, used to observe effects of lncRNA NEAT1/miR‐129‐5p/ KLK7 to papillary thyroid cancer cells. Western blot and qRT‐PCR were used to validate protein expressions and mRNA expressions in PTC tissues and cells. LncRNA NEAT1 was highly expressed in PTC tissues and cell lines and could deteriorate PTC by promoting proliferation, invasion, and migration accompanied by less apoptosis. Besides, miR‐129‐5p/lncRNA NEAT1 were found to negatively correlate with each other by direct target relationship and their combination suppressed the progression of PTC. KLK7, a highly expressed downstream protein in PTC tissues, could be directly regulated by miR‐129‐5p in a negative way. KLK7 accelerated the deterioration of PTC in vitro experiments which could be reversed by sh‐lnc RNA NEAT1 and miR‐129‐5p mimics. In vivo experiments, silence of lncRNA NEAT1 restrain tumor growth in weight and volume. In conclusion, lncRNA NEAT1 suppression could inhibit PTC progression by upregulating miR‐129‐5p, which suppressed KLK7 expression either in vitro or vivo experiments. Abstract : By probing into lncRNA‐NEAT1/miR‐129‐5p/KLK7 interaction, this study would provide new targets for future treatment. In vivo experiments, silence of lncRNA NEAT1 restrain tumor growth in weight and volume. lncRNA NEAT1 suppression could inhibit PTC progression by upregulating miR‐129‐5p, which suppressed KLK7 expression either in vitro or vivo experiments.